2010
DOI: 10.1109/jqe.2010.2046139
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Hysteresis and Thermal Effects in Vertical-Cavity Surface-Emitting Lasers

Abstract: Abstract-We study numerically the polarization-resolved light-output characteristic of vertical-cavity surface-emitting lasers (VCSELs) using the spin-flip model for VCSELs extended to take into account thermal effects via a dynamical equation for the active region temperature, including heat dissipation, heating due to nonradiative carrier recombination, and Joule effect. The temperature dynamics is coupled to the carrier and optical field dynamics via a frequency and temperaturedependent gain coefficient. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The aim of this Letter is to study experimentally and theoretically the influence of the current modulation frequency and the substrate temperature on the VCSEL threshold current and gain a better understanding of thermal effects in VCSELs. The experimental results show that the hysteresis of turn-on and turn-off can be positive or negative, depending on the current modulation frequency and substrate temperature, in good agreement with the numerical results [4]. Numerical simulations that are in good qualitative agreement with the experiments are also presented and allow for a better understanding of the interplay of the time scales of current modulation and thermal dissipation.…”
supporting
confidence: 71%
See 4 more Smart Citations
“…The aim of this Letter is to study experimentally and theoretically the influence of the current modulation frequency and the substrate temperature on the VCSEL threshold current and gain a better understanding of thermal effects in VCSELs. The experimental results show that the hysteresis of turn-on and turn-off can be positive or negative, depending on the current modulation frequency and substrate temperature, in good agreement with the numerical results [4]. Numerical simulations that are in good qualitative agreement with the experiments are also presented and allow for a better understanding of the interplay of the time scales of current modulation and thermal dissipation.…”
supporting
confidence: 71%
“…A recent numerical study [4] has shown thermally induced hysteresis on the laser switch-on and switch-off points, which depends on the relationship between two time scales: that of the current modulation, which results in dynamical hysteresis [5,6], and that of thermal dissipation, which is an additional source of hysteresis that can give either positive or negative [7,8] hysteresis cycles. In positive cycles, the laser turns on at a higher current value than it turns off; in negative cycles, the turn-on occurs at a lower current value than the turn-off.…”
mentioning
confidence: 99%
See 3 more Smart Citations